Uncovering the Knowledge Landscape of Food-Drug Interactions Among Medical Professionals - Sami, Oula Mohammed (Academia Open, 2024)
Background: Drug-food interactions (DFIs) can alter drug pharmacokinetics and pharmacodynamics, impacting patient outcomes. Health care professionals (HCPs) play a critical role in managing these interactions. Specific Background: Despite their significance, the awareness of DFIs among Iraqi medical professionals is inadequately documented. Knowledge Gap: There is a lack of comprehensive studies evaluating the knowledge of DFIs among medical professionals in Iraq, which is crucial for improving patient care and therapeutic efficacy. Aims: This study aimed to evaluate the knowledge of food-drug interactions among Iraqi medical professionals, including medical students, newly graduated doctors, and junior doctors. Methods: A cross-sectional study was conducted using a self-administered questionnaire with 20 questions evaluating knowledge on common DFIs. Results: The study revealed a concerning lack of knowledge about DFIs among participants, with junior doctors scoring an average of 7.1 out of 15, newly graduated doctors 6.38, and sixth-grade medical students 5.27. Only 13% felt knowledgeable about DFIs, while 31.7% acknowledged their insufficient understanding. Notably, knowledge on interactions such as tyramine-rich foods with antidepressants and grapefruit juice with statins was limited. Novelty: This study provides the first comprehensive assessment of DFI knowledge among Iraqi medical professionals, highlighting significant gaps and educational needs. Implications: The findings underscore the necessity for enhanced educational programs targeting DFIs in medical curricula, ensuring HCPs are equipped to counsel patients effectively, thereby improving patient safety and therapeutic outcomes. These results emphasize the importance of targeted educational interventions to bridge the knowledge gap, ultimately contributing to better health outcomes and informed patient care in Iraq. Highlights: Knowledge Gaps: Iraqi medical professionals lack understanding of common food-drug interactions. Education Needed: Enhanced training on interactions is essential in medical curricula. Patient Safety: Improving knowledge will lead to better patient outcomes. Keywords: Food–Drug Interactions, Knowledge, Drug Interaction, Medical Students